2022
DOI: 10.1007/s00330-022-08911-3
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based radiomics signature for identification of invisible basal cisterns changes in tuberculous meningitis: a preliminary multicenter study

Abstract: Objective To develop and evaluate a radiomics signature based on magnetic resonance imaging (MRI) from multicenter datasets for identification of invisible basal cisterns changes in tuberculous meningitis (TBM) patients. Methods Our retrospective study enrolled 184 TBM patients and 187 non-TBM controls from 3 Chinese hospitals (training dataset, 158 TBM patients and 159 non-TBM controls; testing dataset, 26 TBM patients and 28 non-TBM controls). nnU-Net was used to segment basal cisterns in fluid-attenuated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…The evidence from this review shows that in all studies, ML techniques have been an effective and positive approach to facilitating disease diagnosis and prediction. According to the findings of our study, in eight cases of incoming studies, ML algorithms were used to diagnose the disease, and all studies indicated the high ability of ML algorithms to diagnose meningitis diseases 48,49,52,54–56,60,61 . So even in Jeong and colleagues study, it was stated that the ANN model can have better diagnostic performance than a nonspecialist doctor.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…The evidence from this review shows that in all studies, ML techniques have been an effective and positive approach to facilitating disease diagnosis and prediction. According to the findings of our study, in eight cases of incoming studies, ML algorithms were used to diagnose the disease, and all studies indicated the high ability of ML algorithms to diagnose meningitis diseases 48,49,52,54–56,60,61 . So even in Jeong and colleagues study, it was stated that the ANN model can have better diagnostic performance than a nonspecialist doctor.…”
Section: Discussionmentioning
confidence: 69%
“…He concluded that the T2‐weighted radiomic signature (T2WI) developed using the SVM classifier shows special diagnostic significance for TBM that may not be detected by an unaided eye in conventional MR images. Therefore, the automated segmentation of base reservoirs and the developed radiomic signature may provide complementary data to help diagnose TBM in a fully automated manner before the appearance of lesions with visible features 48 . Also, Babenk and his colleagues showed the ability to determine procalcitonin and C‐reactive protein (CRP) with cut‐off values for distinguishing between BM and EVM in children using the fast and cost‐effective decision tree (FFTree) approach.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations